Conflict and Moral Values of Being That Found in the Kung Fu Panda 1 Movie - Ming, Adrian; Winarta, Ida Bagus Gde Nova (Journal of Language and Applied Linguistics, 2025)
This study is aimed to find out the conflict that found in the Kung Fu Panda 1 movie, and to analyze the moral values of being that found in the Kung Fu Panda 1 movie. This movie narrates about a fat panda who has a solid desire about being the greatest warrior. The descriptive qualitative method was used in this research to elaborate the conflict in this movie also, deliver a clear and brief description of the moral values of being. In the data collection, researcher combining between watching and recording techniques. These things are examined using DiYanni (2000) theory to analyze the conflict, and while, Linda & Eyre (1993) to identify the moral values of being in the movie. The subject of this research is the movie entitled Kung Fu Panda 1 by Ethan Reiff and Cyrus Voris. The result of this study showed that are 3 (three) types of conflict that found in the Kung Fu Panda 1 movie, namely between character and themselves, between character and the other characters, and between character and society. Furthermore, there are 5 (five) types of moral values of being, namely honesty, courage, peaceability, self-reliance and potential, and self-discipline and moderation.